The Effect of Seft Virtual Reality Therapy on Anxiety and Sleep Quality of Preoperative Patients - Saharullah Saharullah; Muhammad Ardianto Rodin; Asnuddin Asnuddin; Rusli Taher; Abdul Thalib (GLOBAL HEALTH SCIENCE GROUP, 2025)
Surgical procedures often cause anxiety that has an impact on the impaired sleep quality of preoperative patients. Untreated anxiety can hinder the surgical process and even potentially cancel surgery. Objective: To analyze the effect of Virtual Reality Spiritual Emotional Freedom Technique (VR-SEFT) therapy on the level of anxiety and sleep quality of preoperative patients at the UPT of Lamaddukelleng Hospital, Wajo Regency. The research design used a quasi-experiment with a pre and post test control group design approach. The sample totaled 60 respondents, divided into an intervention group (n=30) and a control group (n=30) through purposive sampling techniques. The intervention group received VR-SEFT therapy twice a day for three days, with a duration of 15 minutes per session, while the control group received standard preoperative treatment. Research instruments include the Hamilton Rating Scale for Anxiety (HARS-A) to measure anxiety (validity coefficients 0.529–0.727; Cronbach’s α = 0.756) and the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality (Cronbach’s α = 0.64–0.83). Data analysis was carried out using univariate and bivariate tests with a significance level of 95% (α=0.05). Results: There was a significant reduction in anxiety and improved sleep quality in the intervention group compared to the control (p<0.001). The average HARS score decreased from 35.67 to 12.83 (control: 37.20 to 23.67), while PSQI from 49.67 to 14.33 (control: 50.77 to 25.27). Effect size showed a very large influence on anxiety (d=4.22) and sleep quality (d=3.19). VR-SEFT is effective in lowering anxiety and improving the sleep quality of preoperative patients, and has the potential to be integrated into perioperative nursing practice. This finding is expected to be an innovation in health services, especially in supporting the achievement of the Sustainable Development Goals (SDGs) point 3, namely improving mental health and patient welfare.